PREDIKSI KEBANGKRUTAN MENGGUNAKAN JARINGAN SARAF BUATAN - Petra, Stradivarius Melvin; Suryantara, I Gusti Ngurah; Tampinongkol, Felliks Feiters (Universitas Bunda Mulia, 2024)
The worst thing about financial failure is bankruptcy. The bankruptcy of a company can be analyzed from financial statements. the results of financial statement analysis is very useful for corporate leaders and investors to know the true condition of the company. Financial statement analysis can be done by calculating financial ratios. This study uses five variable financial ratios to predict corporate bankruptcy with repeated neural networks that apply Elman model. The sample data used in this study are 50 companies listed on the IDX 2007-2010 period. data is divided into two groups, 80% for training data and 20% for test data. Based on the function obtained from the training data, 10 companies will be tested. The best results from testing show that 9 out of 10 got the correct data.